PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 11 PADANG - TITHA MUHARMAN (Departemen Matematika, 2021)
One of them objectives of laerning mathematic is understanding mathematic concepts. However, in reality at SMP Negeri 11 Padang the understanding of these mathematic concepts is still not optimal. One of them eforts that can be madde to improve students’ understand of mathernatic concepts is to apply the (TTW) type of coperative learning model. The purpouse of this researc is to desicribe and nalyse whether the understand of the mathematic concepts of student whom learns us the Think Talk Write (TTW) type of coperative learning model is beter then the understande of mathematic concepts of students who learn using conventional leaming models. This type of researc is a quasy experiment researc with a Static Group Design research design. In this design, the population is all students of class VIII SMP Negri 11 Padang. Sampling was done bye using random sampling tecnique. The researc instrument used was a test of understanding mathematicall concepts. This research hypothesis was conducted using the –t test. Based on the researc result, it waas conloud thats the TTW coperative learning model coulde improve students’ understanding of mathematic concepts. This shows that the effect of the TTW type of coperative learning models on them understanding of them mathematical concepts of students who learn using the TTW type of coperative learning models is beter than the understanding of the mathematic concepts of student who learn using conventional learn in class VIII of SMP Negeri 11 Padang. Keywords — Think Talk Write, Mathematical Concepts.